Transformation of Teacher and School Principal Performance Management - Nurdiansari Nurdiansari; Junainah Junainah; Azainil Azainil (Jurnal Indonesia Sosial Teknologi, 2024)
Performance Management Through the Medeka Mengajar Platform is a tool that makes it easier for teachers and school principals to set more contextual performance targets in accordance with the needs of indicator units and career development to improve the quality of student-centered learning. This Performance Management feature is also integrated with e-performance services managed by the State Civil Service Agency. The method used in this research is the Library Research method or library research. Performance management transformation is a form of collaborative relationship carried out by the Ministry of Education and Culture with teachers and school principals, the State Civil Service Agency (BKN), a government agency in charge of personnel management, and the Regional Government according to its authority through the Regional Personnel Agency and the Education Service. This performance management transformation comes as a form of aligning and accelerating processes through integrated technology in regional performance management. There are relevant performance improvement priority indicators to assist teachers and school principals in achieving them. Assistance from the Ministry of Education and Culture and the Education Department is still needed in managing performance through PMM.